Comfort Evaluation of Double-Sided Catwalk for Suspension Bridge due to Wind-Induced Vibration. (11th March 2021) - Li, Zhi-Guo; Chen, Fan; Pei, Cheng; Zhang, Jia-Ming; Chen, Xin
Abstract : Buffeting response of a double-sided catwalk designed for Maputo Bridge was investigated considering wind load nonlinearity, geometric nonlinearity, and self-excited forces. Buffeting analysis was conducted in time domain using an APDL-developed program in ANSYS, and the results were compared with the buffeting response under the traditional linear method. The wind field was simulated using the spectra representation method. Aerostatic coefficients were obtained from section model wind tunnel test. Parameter study has been carried out to investigate the effects of cross bridge interval and the gantry rope diameter on buffeting response. Referring to the ISO 2631-1(1997) standard and the annoyance rate model, the comfort of catwalk due to wind-induced vibration was evaluated. The results indicate that traditional linear calculation methods will underestimate the buffeting response of the catwalk, and enlarging the gantry rope size as well as decreasing the cross bridge interval would increase the comfort level. Moreover, the effect of gantry rope diameter was obvious than that of cross bridge interval. Annoyance rate model can evaluate the comfort level quantitatively compared to the ISO standard.